A Brief Introduction to Hepatitis E Virus: Structure, Genome Organization & Replication - Zoya Shafat (Open Reading Frame 4 - A Multifunctional Protein of Hepatitis E Virus, 2024)
Hepatitis E virus (HEV) is a small virus belonging to the family Hepeviridae. HEV is the chief cause of acute hepatitis worldwide, causing approximately 20 million infections annually, which results in 60,000 deaths. The genome of HEV is a single-stranded, positive-sense RNA of about 15 kb in length and is categorized into three open reading frames (ORFs): ORF1, ORF2 and ORF3. HEV GT 1 is known to encode an additional fourth reading frame ORF4, which is expressed only during endoplasmic reticulum (ER) stress. The ORF4 is believed to play a critical functional role in the viral replication of HEV GT 1 isolates. Although the disease was discovered in the late 1980s, the precise molecular mechanisms underlying the higher pregnancy mortality associated with HEV remain elusive. The absence of an efficient culture system and a GT 1 animal pregnancy model is a significant barrier to understanding the mechanisms behind HEV-induced pregnancy mortality. This introductory chapter focuses on the morphology, and genomic organization, along with structural and nonstructural proteins of HEV. The information provided in this review on the HEV proteins is likely to assist in understanding the deeper functioning of structural as well as non-structural biology of HEV proteins.